PERENCANAAN STRATEGIS PT TENARIS SPIJ DALAM MENGHADAPI PIPA IMPOR CHINA KE INDONESIA: ANALISIS BALANCED SCORECARD - , Ferizal Ardiansyah, Prof. Mudrajad Kuncoro, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Casing and tubing pipe (OCTG-Oil Country Tubular Goods) player has become more and more, there are 8 manufacturers installed in casing and tubing pipe threading in Indonesia. Three manufacturers have heat-treatment and threading facilities and only five companies have threading facilities only just so they are really depends on traders who bring imports of semi-finished pipe from China to Indonesia. Chinese pipe market share in Indonesia which collaborated with local threading has become greater. Market share of PT Tenaris SPIJ eroded from year to year because of them. Objective in this thesis to measure the performance of company with the balanced scorecard method to obtain a measurement of the company's performance in the face of Chinese pipe imports to Indonesia. This thesis was conducted with the case study approach in PT Tenaris SPIJ. Balanced scorecard method chosen because it provides a framework to translate chosen strategy into strategic target that is comprehensive, coherent, measurable and balanced, through four perspectives: financial, customer, internal business process and learning and growth.